Content curation in the social networks of higher music educations institutions - Urpí Cámara, Montserrat; Guallar, Javier; Rey-Martin, Carina (Revista General de Información y Documentación, 2024)
This study analyses the dissemination and content curation on the social networks of 23 Spanish public higher music schools. The research uses a descriptive methodology, applying observation techniques and content analysis of the centres’ publications on Facebook, X (formerly Twitter), Instagram, and YouTube for three months. It evaluates the presence of the centres on each platform and the proportion of content curation, as well as the themes and techniques used on X and provides examples of good practice. The results show that Twitter is the platform with the highest number of posts although Instagram gets a higher level of engagement from followers. In terms of content curation, more than half of the tweets contain curated content, mainly using summarising, commenting, and extracting techniques. In conclusion, it is observed that the incorporation of content curation in the publications of the centres provides value and contributes to achieving their communication objectives.